An Analysis of English as a Foreign Language (EFL) Learners’ Problems in Speaking Skills Based on Their Perception at Senior High School - Malik, Emylia; Rohmatillah, Rohmatillah; Rahmawati, Istiqomah Nur (research, training and philanthropy institution Natural Aceh, 2025)
This study examines the factors contributing to speaking difficulties among EFL secondary school learners and offers teachers insights for effectively addressing these challenges. The study aims to augment pedagogical techniques to enhance speaking proficiency results. The study utilized a descriptive qualitative methodology, with 30 class XI students chosen to reflect varied experiences and viewpoints. Data has been collected via open-ended surveys and interviews, using thematic analysis to discern patterns and recurring themes. The results indicate that lacking confidence, restricted vocabulary, and an unsupportive classroom atmosphere substantially impede students' speaking skills. Furthermore, students identified the fear of errors and peer evaluation as significant obstacles. The research emphasizes effective measures for enhancement, including participation in English clubs, consistent practice, and cultivating a supportive teaching environment. These findings underscore the significance of customized instructional strategies and inclusive practices that foster an optimal learning environment. This research highlights the essential function of educators in enabling students to surmount speaking difficulties, enhance self-assurance, and improve communication abilities. By tackling these challenges, EFL learners can cultivate the proficiency required to excel in academic and practical environments.